Vous êtes sur la page 1sur 7

ECON 5113 Advanced Microeconomics

Winter 2018
Answers to Selected Exercises Instructor: Kam Yu

The following questions are taken from Geoffrey A. Jehle % to be convex or strictly convex, therefore the utility
and Philip J. Reny (2011) Advanced Microeconomic The- function exists. Moreover, since % (a) = % (b) is convex,
ory, Third Edition, Harlow: Pearson Education Limited. there exists a supporting hyperplane H = {x ∈ Rn+ :
The updated version is available at the course web page: pT x = y} such that a, b ∈ H. Since H is an affine set,
A ⊂ H. This means that every bundle in A is a solution
http://flash.lakeheadu.ca/∼kyu/E5113/Main.html to the utility maximization problem.

Ex. 1.11 Suppose that p ≥ 0 is a limit point of A. Ex. 1.341 Suppose on the contrary that E is bounded
Then for every  > 0, there exists a point q 6= p in above in u, that is, for some p  0, there exists M > 0
(p − , p + ) such that q ∈ A. This means that for ev- such that M ≥ E(p, u) for all u in the domain of E.
ery neighbourhood B (pe) ∈ Rn+ , there is a bundle qe in Let u∗ = V (p, M ). Then
B (pe) ∩ % (x). Hence pe is a limit point of % (x). Since
% is continuous so that % (x) is a closed set, pe ∈ % (x), E(p, u∗ ) = E(p, V (p, M )) = M = pT x∗ ,
which implies that p ∈ A. Therefore A is closed. The
where x∗ is the optimal bundle. Since U is continuous,
proof for set B is similar.
there exists a bundle x0 in the neighbourhood of x∗ such
that U (x0 ) = u0 > u∗ . Since U strictly increasing, E is
Ex. 1.14 Let U be a continuous utility function that
strictly increasing in u, so that E(p, u0 ) > E(p, u∗ ) =
represents %. Then for all x, y ∈ Rn+ , x % y if and only
M . This contradicts the assumption that M is an upper
if U (x) ≥ U (y).
bound.
First, suppose x, y ∈ Rn+ . Then U (x) ≥ U (y) or
U (y) ≥ U (x), which means that x % y or y % x. There-
Ex. 1.37 (a) Since x0 is the solution of the expenditure
fore % is complete.
minimization problem when the price is p0 and utility
Second, suppose x % y and y % z. Then U (x) ≥ U (y)
level u0 , it must satisfy the constraint U (x0 ) ≥ u0 . Now
and U (y) ≥ U (z). This implies that U (x) ≥ U (z) and
by definition E(p, u0 ) is the minimized expenditure when
so x % z, which shows that % is transitive.
price is p, it must be less than or equal to pT x0 since
Finally, let x ∈ Rn+ and U (x) = u. Then
x0 is in the feasible set, and by definition equal when
U −1 ([u, ∞)) = {z ∈ Rn+ : U (z) ≥ u} p = p0 .
(b) Since f (p) ≤ 0 for all p  0 and f (p0 ) = 0, it
= {z ∈ Rn+ : z % x}
must attain its maximum value at p = p0 .
= % (x). (c) ∇f (p0 ) = 0.
(d) We have
Since [u, ∞) is closed and U is continuous, % (x) is closed.
Similarly (I suggest you to try this), - (x) is also closed. ∇f (p0 ) = ∇p E(p0 , u0 ) − x0 = 0,
This shows that % is continuous.
which gives Shephard’s lemma.
Ex. 1.17 Suppose that a and b are two distinct bundle
such that a ∼ b. Let Ex. 1.46 Since di is homogeneous of degree zero in p
and y, for any α > 0 and for i = 1, . . . , n,
A = {x ∈ Rn+ : αa + (1 − α)b, 0 ≤ α ≤ 1}.
di (αp, αy) = di (p, y).
and suppose that for all x ∈ A, x ∼ a. Then % is convex
but not strictly convex. Theorem 1.1 does not require 1 It may be helpful to review the proof of Theorem 1.8.
Differentiate both sides with respect to α, we have (a) The Lagrangian is
n
∂di (αp, αy) Y
∇p di (αp, αy)T p + y = 0. L=A xα T
i − λ(p x − y).
i
∂y
i=1

Put α = 1 and rewrite the dot product in summation The necessary conditions for maximization are the bud-
form, the above equation becomes get constraint and
Qn
n
∂di (p, y) ∂di (p, y) ∂L xα i
= αj A i=1 i − λpj = 0,
X
pj + y = 0. (1)
∂pj ∂y ∂xj xj
j=1
for j = 1, . . . , n. Consider two goods i and j, the above
Dividing each term by di (p, y) yields the result. necessary condition implies that

Ex. 1.47 Suppose that U (x) is a linearly homogeneous αi /xi pi


= ,
utility function. αj /xj pj
(a) Then
which can be rearranged to
T
E(p, u) = min{p x : U (x) ≥ u}
  
x
αj pi
xj = xi .
= min{upT x/u : U (x/u) ≥ 1} αi pj
x
Substitute this relation for j = 1, . . . , n in the budget
= u min{pT x/u : U (x/u) ≥ 1}
x constraint, we have
= u min{pT x/u : U (x/u) ≥ 1} (2)      
x/u α1 pi αn pi
p1 xi +· · ·+pi xi +· · ·+pn xi = y,
= u min{pT z : U (z) ≥ 1} (3) αi p1 αi pn
z
or
= uE(p, 1)  n
 X !
pi
= ue(p) αk xi = y.
αi
k=1
In (2) above it does not matter if we choose x or x/u Since Pn αk = 1, the above equation gives the Mar-
k=1
directly as long as the objective function and the con- shallian demand function of good i as
straint remain the same. We can do this because of the
αi y
objective function is linear in x. In (3) we simply rewrite di (p, y) = xi = ,
x/u as z. pi
(b) Using the duality relation between V and E and for i = 1, . . . , n.
the result from Part (a) we have
Ex. 1.66 (b) By definition y 0 = E(p0 , u0 ), Therefore
y = E(p, V (p, y)) = V (p, y)e(p)
y1 E(p1 , u0 )
so that >
y y0 E(p0 , u0 )
V (p, y) = = v(p)y,
e(p) means that y 1 > E(p1 , u0 ). Since the indirect utility
where we have let v(p) = 1/e(p). The marginal utility function V is increasing in income y, it follows that
of income is u1 = V (p1 , y 1 ) > V (p1 , E(p1 , u0 )) = u0 .
∂V (p, y)
= v(p),
∂y
which depends on p but not on y. Ex. 1.67 It is straight forward to derive the expenditure
function, which is
Ex. 1.54 The utility maximization problem is p22
E(p, u) = p2 u − . (4)
n
Y 4p1
max A xα
i
i
x
i=1
(a) For p0 = (1, 2) and y 0 = 10, we can use (4) to
T obtain u0 = 11/2. Therefore, with p1 = (2, 1),
subject to p x = y,
Pn u0 − 1/8 43
where A > 0 and I= = .
i=1 αi = 1. 2u0 − 1 80

2
(b) It is clear from part (a) that I depends on u0 . with the first-order conditions
(c) Using the technique similar to Exercise 1.47, it can
be shown that if U is homothetic, E(p, u) = e(p)g(u), −αpα−1
1 pβ2 + λx1 = 0
where g is an increasing function. Then
and
β−1
e(p1 )g(u0 ) e(p1 ) −βpα 1 p2 + λx2 = 0.
I= 0 0
= 0
,
e(p )g(u ) e(p ) Eliminating λ from the first-order conditions gives
which means that I is independent of the reference utility β x1
level. p2 = p1 .
α x2
Ex. 2.1 Consider the case of one good. Let the demand Substitute this p2 into the constraint equation, we get
function be √
y α 1
d(p, y) = √ . p1 = ,
p α + β x1
It is homogenous of degree zero but it does not satisfy and
budget balancedness. β 1
p2 = .
Conversely, consider the two-good case that the de- α + β x2
mand function is given by The utility function is therefore
 
y log p2 y log p1
αα β β
 
d(p, y) = , . −β
p1 log p2 + p2 log p1 p1 log p2 + p2 log p1 U (x) = x−α
1 x2 ,
(α + β)α+β
Then
which is a Cobb-Douglas function.
yp1 log p2 yp2 log p1
p · d(p, y) = +
p1 log p2 + p2 log p1 p1 log p2 + p2 log p1 Ex. 2.6 We want to maximize utility u subject to the
= y constraint pT x ≥ E(p, u) for all p ∈ Rn++ . That is,

and therefore satisfies budget balancedness. It is straight up1 p2


p1 x1 + p2 x2 ≥ .
forward to verify that d(p, y) is not a homogenous func- p1 + p2
tion.
Rearranging gives
Ex. 2.2 For i = 1, . . . , n, the i-th row of the matrix p1 + p2 p1 + p2
multiplication S(p, y)p is u≤ x1 + x2
p2 p1
n 
for all p ∈ Rn++ . This implies that

X ∂di (p, y) ∂di (p, y)
pj + pj dj (p, y)
j=i
∂pj ∂y  
p1 + p2 p1 + p2
n n u ≤ min x1 + x2 . (7)
X ∂di (p, y) ∂di (p, y) X p1 ,p2 p2 p1
= pj + pj dj (p, y)
j=i
∂pj ∂y j=i Therefore u attains its maximum value when equality
n
X ∂di (p, y) ∂di (p, y) holds in (7). To find the minimum value on the right-
= pj + y (5) hand side of (7), write α = p /(p + p ) so that 1 − α =
j=i
∂pj ∂y 2 1 2
p1 /(p1 + p2 ) and 0 < α < 1. The minimization problem
=0 (6) becomes
 
where in (5) we have used the budget balancedness and x1 x2
min + :0<α<1 . (8)
(6) holds because of homogeneity and (1) in Ex. 1.46. α α 1−α

Ex. 2.3 By (T.1’) on p. 82, Notice that for any x1 > 0 and x2 > 0,
 
U (x) = min {V (p, 1) : p · x = 1} . x1 x2
n
p∈R++
lim + =∞
α→0 α 1−α
The Lagrangian is and  
x1 x2
L = −pα β lim + =∞
1 p2 − λ(1 − p1 x1 − p2 x2 ), α→1 α 1−α

3
P
so that the minimum value exists when 0 < α < 1. The where y = i yi is aggregate income. It is clear that
first-order condition for minimization is market demand depends on aggregate income y but not
x1 x2 on income distribution. The market level income elastic-
− + = 0, ity of demand for good j is
α2 (1 − α)2

which can be written as ∂(fj (p)y) y


ηj = = 1.
∂y fj (p)y
α2 x2 = (1 − α)2 x1 .
Ex. 4.2 If preferences are homothetic but not identical,
Taking the square root on both sides gives the demand function of consumer i is
1/2 1/2
αx2 = (1 − α)x1 . di (p, yi ) = f i (p)yi .
Rearranging gives Market demand is therefore
1/2 1/2
x1 x2
X X
α= and 1−α= . di (p, yi ) = f i (p)yi .
1/2 1/2 1/2 1/2
x1 + x2 x1 + x2 i i

It is clear that α is indeed between 0 and 1. Putting α In this case market demand depends on income distribu-
and 1−α into the objective function in (8) give the direct tion.
utility function
Ex. 4.5 Let w be the vector of factor prices and p
 2
1/2 1/2
U (x1 , x2 ) = x1 + x2 , be the output price. Then the cost function of a typ-
ical firm with constant returns-to-scale technology is
C(w, y) = c(w)y where c is the unit cost function. The
which is the CES function with ρ = 1/2. You should
profit maximization problem can be written as
verify with Example 1.3 on p. 39–41 that the expenditure
function is indeed as given. max py − c(w)y = max y[p − c(w)].
y y
Ex. 3.2 Constant returns-to-scale means that f is lin-
early homogeneous. So by Euler’s theorem For a competitive firm, as long as p > c(w), the firm will
increase output level y indefinitely. If p < c(w), profit
x1 ∂y/∂x1 + x2 ∂y/∂x2 = y. (9) is negative at any level of output except when y = 0.
If p = c(w), profit is zero at any level of output. In
Since average product y/x1 is rising, its derivative respect fact, market price, average cost, and marginal cost are
to x1 is positive, that is, all equal so that the inverse supply function is a constant
function of y. Therefore the supply function of the firm
(x1 ∂y/∂x1 − y)/x21 > 0. does not exist and the number of firm is indeterminate.

From (9) we have Ex. 4.7 Suppose that all firms have the same technology
and therefore the same cost function. Given market price
x2 ∂y/∂x2 = −(x1 ∂y/∂x1 − y) < 0,
p, profit of a typical firm j is pqj − c(qj ).
which means that the marginal product ∂y/∂x2 is nega- (a) Suppose that a > 0, b < 0, and there are J firms in
tive. the industry. The short-run profit maximization for firm
j is !
J
Ex. 4.1 If preferences are identical and homothetic, each X
max α − β qi qj − (aqj + bqj2 ).
consumer’s preferences can be represented by a linearly qj
i=1
homogeneous utility function. Using an argument sim-
ilar to exercise 1.47, the ordinary demand function of The necessary condition for profit maximization is
consumer i is separable in p and yi , that is, J
X
i
d (p, yi ) = f (p)yi . α − βqj − β qi − a − 2bqj = 0. (10)
i=1

Market demand is therefore


By symmetry, q1 = q2 = · · · = qJ . Equation (10) be-
X
di (p, yi ) = f (p)
X
yi = f (p)y, comes
i i
α − β(J + 1)qj − a − 2bqj = 0,

4
which gives (b) Suppose that both firms have fixed costs F > 0.
α−a Then both firms stay in production in equilibrium and
qj = .
β(J + 1) + 2b charge a price equal to the solution in equation (12).
The market output is They share the market with q1 = q2 = (α−βp)/2. Notice
that in equation (12), p = c is the solution if F = 0.
J(α − a) (c) If firm 1 has a lower marginal cost so that c2 >
q= ,
β(J + 1) + 2b c1 > 0, then firm 1 will charge a price p1 = c2 just to
keep firm 2 out of the market. Therefore q2 = 0 and
and the market price is q1 = α − βc2 .
βJ(α − a)
p=α− , Ex. 4.14 The profit maximization problem for a typical
β(J + 1) + 2b
firm is
(b) The average cost of production is
max [10 − 15q − (J − 1)q̄]q − (q 2 + 1),
q
c(q)
= a + bq,
q with necessary condition

which is a decreasing function if a > 0 and b < 0. Since 10 − 15q − (J − 1)q̄ − 15q − 2q = 0.
there is no fixed cost, a firm can potentially increase out-
put until the average (or total) cost of production is zero, (a) Since all firms are identical, by symmetry q = q̄.
which is at the output level q = −a/b. Notice that at zero This gives the Cournot equilibrium of each firm q ∗ =
market price, consumer demand is α/β. Therefore the 10/(J + 31), with market price p∗ = 170/(J + 31).
long-run equilibrium market price and number of firms (b) Short-run profit of each firm is π = [40/(J +31)]2 −
depend on the relative values of −a/b and α/β. 1. In the long-run π = 0 so that J = 9.
(c) If a > 0 and b > 0, the minimum efficiency scale
is at q = 0. Therefore the long-run equilibrium market Ex. 4.19 The Marshallian demands are x∗ = 1/p and
price and number of firms are indeterminate. m∗ = y − 1. The indirect utility function is V (p, y) =
y − log p − 1. If the price of x rises from p0 to p1 , the
Ex. 4.12 In the Bertrand duopoly model of section 4.2.1, compensating variation is implicitly defined as
the firms have no fixed costs and equal marginal cost c.
V (p1 , y + CV) = V (p0 , y),
In equilibrium both firms charge p = c and share the
market equally. or
(a) Now suppose that firm 1 has fixed costs F > 0. If y + CV − log p1 − 1 = y − log p0 − 1.
it stays in production, in equilibrium the price it charges 1 0
must be the same as firm 2. This implies that p1 = p2 = This gives CV = log(p /p ), which is equal to the change
p. But the zero profit condition for firm 1 is in consumer surplus.

pq1 − cq1 − F = 0, Ex. 5.11 (a) The necessary condition for a Pareto-
efficient allocation is that the consumers’ MRS are equal.
or Therefore
F
p=c+ > c.
q1 ∂U 1 (x11 , x12 )/∂x11 ∂U 2 (x21 , x22 )/∂x21
= ,
Assume that the firm share the market equally, q1 = q2 = ∂U 1 (x11 , x12 )/∂x12 ∂U 2 (x21 , x22 )/∂x22
Q/2 so that or
x12 x22
2F 2F = . (13)
p=c+ =c+ . (11) x11 2x21
Q α − βp
The feasibility conditions for the two goods are
Since firm 2 has no fixed cost, it can charge a price
slightly lower than this and capture the whole market. x11 + x21 = e11 + e21 = 18 + 3 = 21, (14)
In equilibrium firm 2 charges a price that satisfies equa- 1 2 1 2
x2 + x2 = e2 + e2 = 4 + 6 = 10. (15)
tion (11), which can be rearranged to the quadratic equa-
tion Express x21 in (14) and x22 in (15) in terms of x11 and x12
2
βp − (α + βc)p + (αc + 2F ) = 0. (12) respectively, (13) becomes
Therefore p2 = p, the solution in equation (12), q1 = 0, x12 10 − x12
and q2 = α − βp. = ,
x11 2(21 − x11 )

5
is given by
10x11

C(e) = (x11 , x12 , x21 , x22 ) : x12 = ,
42 − x11
14.16 ≤ x11 ≤ 15.21, x11 + x21 = 21,
x12 + x22 = 10.

(c) Normalize the price of good 2 to p2 = 1. The


demand functions of the two consumers are:
y1 p1 e11 + p2 e12 18p1 + 4
x11 = = =
2p1 2p1 2p1
y1 p1 e11 + p2 e12 18p1 + 4
x12 = = =
2p2 2p2 2
y2 2
p1 e1 + p2 e2 2
3p1 + 6
Figure 1: Contract Curve and the Core x21 = = =
3p1 3p1 3p1
2y 2 2 2
2(p1 e1 + p2 e2 ) 2(3p1 + 6)
x22 = = =
or 3p2 3p2 3
10x11 In equilibrium, excess demand z1 (p) for good 1 is zero.
x12 = . (16)
42 − x11 Therefore
18p1 + 4 3p1 + 6
Eq. (16) with domain 0 ≤ x11 ≤ 21, (14), and (15) com- + − 18 − 3 = 0,
2p1 3p1
pletely characterize the set of Pareto-efficient allocations
A (contract curve). That is, which gives p1 = 4/11 (check that market 2 also clears).
The Walrasian equilibrium is p = (p1 , p2 ) = (4/11, 1).
10x11 From the demand functions above, the WEA is

1 1 2 2 1 1
A = (x1 , x2 , x1 , x2 ) : x2 = , 0 ≤ x1 ≤ 21,
42 − x11
x = (x11 , x12 , x21 , x22 ) = (14.5, 5.27, 5.6, 4.73).
1 2 1 2

x1 + x1 = 21, x2 + x2 = 10.
(d) It is easy to verify that x ∈ C(e).
(b) The core is the section of the curve in (16) be-
tween the points of intersections with the consumers’ in- Ex. 5.23 Let Y ⊆ Rn be a strongly convex production
difference curves passing through the endowment point. set. For any p ∈ Rn++ , let y1 ∈ Y and y2 ∈ Y be two
For example, in Figure 1, if G is the endowment point, distinct profit-maximizing production plans. Therefore
the core is the portion of the contract curve between p · y1 = p · y2 ≥ p · y for all y ∈ Y . Since Y is strongly
points W and Z. Consumer 1’s indifference curve passing convex, there exists a ȳ ∈ Y such that for all t ∈ (0, 1),
through the endowment is ȳ > ty1 + (1 − t)y2 .

(x11 x12 )2 = (18 · 4)2 , Thus


p · ȳ > tp · y1 + (1 − t)p · y2
or x12 = 72/x11 . Substituting this into (16) and rearrang-
ing give = tp · y1 + (1 − t)p · y1
5(x11 )2 + 36x11 − 1512 = 0. = p · y1 ,

Solving the quadratic equation gives one positive value which contradicts the assumption that y1 is profit-
of 14.16. Consumer 2’s utility function can be written maximizing. Therefore y1 = y2 .
as x21 (x22 )2 . This can be expressed in terms of x11 and
x12 using (14) and (15). The indifference curve passing Ex. 5.31 Let E = {(U i , ei , θij , Y j )|i ∈ I, j ∈ J } be
through endowment becomes the production economy and p ∈ Rn++ be the Walrasian
equilibrium.
(a) For any consumer i ∈ I, the utility maximization
(21 − x11 )(10 − x12 )2 = (21 − 18)(10 − 4)2 = 108.
problem is
Putting x12 in (16) into the above equation and solving
X
max U i (x) s. t. p · x = p · ei + θij π j (p),
for x11 give x11 = 15.21. Therefore the core of the economy x
j∈J

6
with necessary condition

∇U i (x) = λp.

The MRS between two goods l and m is therefore

∂U i (x)/∂xl pl
i
= .
∂U (x)/∂xm pm

Since all consumers observe the same prices, the MRS is


the same for each consumer.
(b) Similar to part (a) by considering the profit maxi-
mization problem of any firm.
(c) This shows that the Walrasian equilibrium prices
play the key role in the functioning of a production econ-
omy. Exchanges are impersonal. Each consumer only
need to know her preferences and each firm its produc-
tion set. All agents in the economy observe the common
price signal and make their own decisions. This mini-
mal information requirement leads to the lowest possible
transaction costs of the economy.

Other Exercises
Theorem 2.1 Here is a suggested proof that the utility
function generated by the expenditure function is un-
bounded:
On the contrary suppose that U is bounded. That is,
there exists a utility level ū such that for all x ∈ Rn+ ,
U (x) ≤ ū. Let u0 > ū and p0  0. Then by the
concavity of E in p, for any p  0,

E(p, u0 ) ≤ E(p0 , u0 ) + ∇p E(p0 , u0 )T (p − p0 )


= E(p0 , u0 ) + ∇p E(p0 , u0 )T p
−∇p E(p0 , u0 )T p0
= E(p0 , u0 ) + ∇p E(p0 , u0 )T p − E(p0 , u0 )
= ∇p E(p0 , u0 )T p,

where in the second last equality we apply Euler’s theo-


rem to E since it is linearly homogeneous in p. Define
x0 = ∇p E(p0 , u0 ) so that we have E(p, u0 ) ≤ pT x0 for
all p  0. In other words, u0 is feasibility set of the
maximization problem

U (x0 ) = max{u : pT x0 ≥ E(p, u) ∀ p  0}.

Therefore U (x0 ) ≥ u0 , which contradicts the assumption


that ū is an upper bound of U .

2017
c The Pigman Inc. All Rights Reserved.